Advanced chronic kidney disease, end‐stage renal disease and renal death among HIV‐positive individuals in Europe. Issue 8 (16th April 2013) - Ryom, L; Kirk, O; Lundgren, JD; Reiss, P; Pedersen, C; De Wit, S; Buzunova, S; Gasiorowski, J; Gatell, JM; Mocroft, A; ,
<x xml:space="preserve">Abstract</x> Objectives Knowledge about advanced chronic kidney disease (CKD) and end‐stage renal disease (ESRD) in HIV‐positive persons is limited. The aim of this study was to investigate incidence, predictors and outcomes for advanced CKD/ESRD and renal death. Methods Advanced CKD was defined as confirmed (two consecutive measurements ≥ 3 months apart) estimated glomerular filtration rate (eGFR) ≤ 30 mL/min/1.73 m2 using Cockcroft−Gault, and ESRD as haemodialysis or peritoneal dialysis for ≥ 1 month or renal transplant. Renal death was death with renal disease as the underlying cause, using Coding Causes of Death in HIV (CoDe) methodology. Follow‐up was from 1 January 2004 until last eGFR measurement, advanced CKD, ESRD or renal death, whichever occurred first. Poisson regression was used to identify predictors. Results Of 9044 individuals included in the study, 58 (0.64%) experienced advanced CKD/ESRD/renal death [incidence rate 1.32/1000 person‐years of follow‐up (PYFU); 95% confidence interval (CI) 0.98–1.66]; 52% of those who experienced the endpoint had a baseline eGFR ≤ 60 mL/min/1.73 m2 compared with 3% of those who did not. Using Kaplan−Meier methods, at 6 years from baseline, 0.83% (95% CI 0.59–1.07%) were estimated to have experienced the endpoint overall and 11.26% (95% CI 6.75–15.78%) among those with baseline eGFR ≤ 60 mL/min/1.73 m2. Independent predictors of the endpoint included any cardiovascular event [incidence rate ratio (IRR) 2.16; 95% CI 1.24–3.77], lower eGFR (IRR 0.64 per 5 mL/min/1.73 m2; 95% CI 0.59–0.70) and lower CD4 count (IRR 0.77 per doubling; 95% CI 0.62–0.95). One year after experiencing advanced CKD or ESRD, an estimated 19.21% (95% CI 7.84–30.58%) of patients had died, mostly from extra‐renal causes. Conclusions The incidence of advanced CKD/ESRD/renal death was low and predictors included traditional renal risk factors, HIV‐related factors and pre‐existing renal impairment. The prognosis following advanced CKD/ESRD was poor. Larger studies should address possible contributions of specific antiretrovirals.